The origin of the atomic and molecular gas contents of early-type galaxies – II. Misaligned gas accretion. Issue 2 (12th February 2015) - Lagos, Claudia del P.; Padilla, Nelson D.; Davis, Timothy A.; Lacey, Cedric G.; Baugh, Carlton M.; Gonzalez-Perez, Violeta; Zwaan, Martin A.; Contreras, Sergio
Abstract : We study the origin of the wide distribution of angles between the angular momenta of the stellar and gas components, αG, S, in early-type galaxies (ETGs). We use the GALFORM model of galaxy formation, set in the Λ cold dark matter framework, and coupled it with a Monte Carlo simulation to follow the angular momenta flips driven by matter accretion on to haloes and galaxies. We consider a gas disc to be misaligned with respect to the stellar body if αG, S  > 30 deg. By assuming that the only sources of misalignments in galaxies are galaxy mergers, we place a lower limit of 2–5 per cent on the fraction of ETGs with misaligned gas/stellar components. These low fractions are inconsistent with the observed value of ≈42 ± 6 per cent in ATLAS 3D . In the more general case, in which smooth gas accretion in addition to galaxy mergers can drive misalignments, our calculation predicts that ≈46 per cent of ETGs have αG, S  > 30 deg. In this calculation, we find correlations between αG, S and stellar mass, cold gas fraction and star formation rate, such that ETGs with high masses, low cold gas fractions and low star formation rates are more likely to display aligned cold gas and stellar components. We confirm these trends observationally for the first time using ATLAS 3D data. We argue that the high fraction of misaligned gas discs observed in ETGs is mostly due to smooth gas accretion (e.g. cooling from the hot halo of galaxies) which takes place after most of the stellar mass of the galaxy is in place and comes misaligned with respect to the stellar component. Galaxies that have accreted most of their cold gas content prior to the time where most of the stellar mass was in place show aligned components.